Pengaruh Model Pembelajaran Project Based Learning (Pjbl) Terhadap Motivasi Belajar Pai Pada Peserta Didik Kelas VIII C Di SMP N 1 Karawang Barat - Suaidah, Annida; Sitika, Achmad Junaedi; Nurhasan, Nurhasan (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of using the Project Based Learning (PjBL) learning model on the motivation to learn PAI in class IIC students at SMPN 1 Karawang Barat. The method used in this study is the correlation method. The population is all students of class VIII SMPN 1 West Karawang. By using the Purposive Sampling Technique, the sample selected was in class IIC SMPN 1 West Karawang with 40 students. Instruments in the research used were observation, questionnaires, and documentation. Data analysis techniques in this study were the normality test, homogeneity test, linearity test, and hypothesis testing (t test, correlation test, determination test and simple linear regression test). Based on the correlation calculation, a significance value of less than 0.05 is obtained, namely 0.000 (0.000 <0.05). This shows that Ho is rejected and Ha is accepted, which means that there is a significant influence between the Project Based Learning learning model on the motivation to learn PAI in class IIC students at SMPN 1 Karawang Barat.